(untitled) (SAARC Journal of Agriculture, 2019)
The experiment was conducted on fresh broiler meat treated with 60Co gamma irradiation having dose of 0 (T0), 1 (T1), 2 (T2) and 3.5 kGy (T3)) and stored 0, 30 and 60 days at -20ºC to estimate the effect on proximate, sensory, physicochemical, biochemical and microbial changes in broiler meat. Factorial experiment (4x3) in completely randomized design (CRD) replicated three times per cell was applied to study the variation among treatment combination. Color was changed significantly (p<0.05) with higher irradiation doses. DM, EE, CP was increased, and Ash and pH was decreased significantly (p<0.05) with higher irradiation doses. Thiobarbituric acid reactive substances (TBARS), Peroxide value (PV), Free fatty acid (FFA), cooking loss was increased significantly (p<0.05) with irradiation level and storage period. Total viable count (TVC), Total coliform count (TCC), Total yeast and mold count (TYMC) was significantly (p<0.05) reduced with irradiation level. Considering all traits it can be concluded that irradiation significantly decreased microbial population and maintain nutritional quality of broiler meat. The irradiation dose 2.0 kGy showed most acceptable for microbial population reduction, maintains overall acceptability and for shelf life extension of broiler meat comparison to non-irradiated meat sample. SAARC J. Agri., 17(1): 149-159 (2019)